Bangladesh national culture and heritage : an introductory reader - Ahmed, A. F. Salahuddin; Chowdhury, Bazlul Mobin; Khan, A. Majeed; Chowdhury, Abdul Momin; Shahed, Syed Mohammad (University Press Limited, 2022)
Contributed articles on history and civilization of Bangladesh in 19th and 20th century.